PROGRAM BIMBINGAN PRIBADI SOSIAL UNTUK PENINGKATAN KEPERCAYAAN DIRI SISWA - Dani Tohir (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2016)
This research is based on a phenomena of students who have low self-confidence. This self-confidence is very important as an investment in processing student’s self-develop. Furthermore, there’s no guidance and counseling programme related to improving students’ self-confidence in MTs. Al Bidayah. The purpose of this research is to develop a programme of social personal guidance for improving students’ self-confidence and to gain insight of the effectivity of this programme. The method used is pre-experiment and the participants of this research are 63 students of year 8 in MTs. Al Bidayah Bandung Barat District. Simple random sampling was used to choose the participants and try out applied to 11 students who have low self-confidence to recognize the effectivity of programme. Data collection method used is questionnaire. The research result shows that (1) this guidance programme to improve students’ self-confidence consists of direction and values, motivation, emotional stability, a positive mind-set, self-awareness, flexibility in behavior, eagerness to develop, mentally health and energy, a willingness to take risks, and a sense of purpose; (2) on paired sample t-test shows thitung which is -5.123 while ttabel with ? = 0.05 and df n – 1= (11 - 1 = 10) equal to 1.812. in the other words, social personal guidance programme is effective to improve students’ self-confidence in year 8 of MTs. Al Bidayah Bandung Barat District.